Pengaruh Metode Mind Mapping Terhadap Kemampuan Membaca Intensif Siswa Kelas XII Sekolah Menengah Atas - Yayan Sudrajat; Munzir Munzir (Faktor Jurnal Ilmiah Kependidikan, 2018)
Abstract: The purpose this study  to determine the effect of using Mind Mapping learning methods on students' intensive reading skills. This experimental research  to stimulate students' intensive reading skills. The test instrument consists of 20 items, memory (C1),understanding (C2),application (C3),and analysis (C4). Data analysis with the Independent Sample T-Test (SPSS 25) obtained sig.(2 tailed) 0,000 <0,005, then Ho was rejected and HA was accepted, there were differences in the average intensive reading ability of students post-test experiment and post-test control. In pair 1 There is a difference in the average students' intensive reading ability in pre-tests and post-test Mind Mapping experiments. In pair 2, it was obtained sig.(2-tailed) of 0.000 <0.05, so there was a difference in students' intensive reading ability in the pre-test-control with the post-test control class. Independent Sample T-test  showed an increase in experiment pre-test value of 76.76 increased to 76.91 seen from the paired sample statistics table.Key Word : Mind Mapping, intensive reading